Explaining NOMAD D/H Observations by Cloud‐Induced Fractionation of Water Vapor on Mars. Issue 2 (10th February 2022) - Daerden, F.; Neary, L.; Villanueva, G.; Liuzzi, G.; Aoki, S.; Clancy, R. T.; Whiteway, J. A.; Sandor, B. J.; Smith, M. D.; Wolff, M. J.; Pankine, A.; Khayat, A.; et al.
Abstract: The vertical profiles of water vapor and its semi‐heavy hydrogen isotope HDO provided by instruments on ExoMars Trace Gas Orbiter constitute a unique new data set to understand the Martian water cycle including its isotopic composition. As water vapor undergoes hydrogen isotopic fractionation upon deposition (but not sublimation), the D/H isotopic ratio in water is a tracer of phase transitions, and a key quantity to understand the long‐term history of water on Mars. Here, we present 3D global simulations of D/H in water vapor and compare them to the vertically resolved observations of D/H and water ice clouds taken by NOMAD during the second half of Mars year 34. D/H is predicted to be constant with height up to the main cloud level, above which it drops because of strong fractionation, explaining the upper cut‐off in the NOMAD observations when HDO drops below detectability. During the global and regional dust storms of 2018/2019, we find that HDO ascends with H2 O, and that the D/H ratio is constant and detectable up to larger heights. The simulations are within the provided observational uncertainties over wide ranges in season, latitude and height. Our work provides evidence that the variability of the D/H ratio in the lower and middle atmosphere of Mars is controlled by fractionation on water ice clouds, and thus modulated by diurnally and seasonally varying cloud formation. We find no evidence of other processes or reservoirs that would have a significant impact on the D/H ratio in water vapor. Plain Language Summary: The isotopic composition of atmospheric water on Mars provides insights about the phase transitions in the water cycle, because the light (H2 O) and semi‐heavy (HDO) form of water vapor deposit at different saturation pressures. Knowing the isotopic composition of atmospheric water also provides insights on the long‐term evolution of water on Mars. The NOMAD instrument on ExoMars Trace Gas Orbiter provided the first vertical profiles of the D/H ratio in water vapor on Mars. The data set shows a large variability with season and latitude. To understand this behavior, a general circulation model is required. We provide detailed simulations of the D/H ratio in Martian water vapor and compare them with the NOMAD observations. The model predicts that the D/H ratio is constant in the lower atmosphere and decreases across a layer of strong cloud formation that varies with season. During the global dust storm of 2018, this cloud layer was severely lifted. The simulations compare well to the observations, both out and in the dust storm, and explain their upper cut‐off by this predicted decrease in D/H. No other processes than cloud formation, nor special surface ice reservoirs with strongly different D/H values, were needed to reproduce the observations. Key Points: Hydrogen fractionation by clouds in Mars water vapor is simulated and evaluated with NOMAD D/H observations in and out of dust storms The model D/H ratio is constant and drops when clouds form, explaining the upper cut‐off in the NOMAD profiles as HDO becomes undetectable NOMAD water ice observations provide evidence that fractionation by clouds is the main factor controlling the HDO distribution on Mars